Sanitation Control of Ferry Ports in Tanjung Harapan Harbor - Pramawati, Anita; Novelasari, Novelasari; Aryanti, Aryanti; Lubis, Abdillah (Newinera Publisher, 2024)
Environmental sanitation is an activity to create healthy environmental conditions in the port area. Good sanitation conditions can prevent disease transmission. Sanitary conditions in the Port of Tanjung Harapan Selat Panjang are not good enough, characterized by rat catching which increases every year, poor drainage conditions, and inadequate sanitation facilities. The purpose of this study is to evaluate the management of sanitation at Tanjung Harapan Harbor in Selat Panjang to become input material to make it better in the future. This research uses a qualitative method with a system approach based on input, process and output where the data collected comes from interviews, observation and documentation and is analyzed using triangulation. Sanitary management of the Port of Tanjung Harapan Selat Panjang is managed by port management and supervised by the Port Health Office. Sanitary management at the Port of Tanjung Harapan Selat Panjang is already running but not optimal, there are still obstacles from the aspects of human resources, large financing and inadequate infrastructure such as the unavailability of TPS and WWTP for waste management. Port sanitation management must be maintained to prevent the development of disease vectors and transmission of various types of diseases. The need for good cooperation between the manager and the Port Health Office to create a healthy port.